Predicting initiation and progression of chronic kidney disease: Developing renal risk scores - Taal, M.W.; Brenner, B.M. (Kidney international, 2006)
Epidemiological studies have raised awareness of the problem of undiagnosed chronic kidney disease (CKD) and suggest that early identification and treatment will reduce the global burden of patients requiring dialysis. This has highlighted the twin problems of how to identify subjects for screening and target intervention to those with CKD most likely to progress to end-stage renal disease. Prospective studies have identified risk factors for CKD in the general population as well as risk factors for progression in patients with established CKD. Risk factors may thus be divided into initiating factors and perpetuating factors, with some overlap between the groups. In this paper, we review current data regarding CKD risk factors and illustrate how each may impact upon the mechanisms underlying CKD progression to accelerate loss of renal function. We propose that these risk factors should be used as a basis for developing a renal risk score, analogous to the Framingham risk score for ischemic heart disease, which will allow accurate determination of renal risk in the general population and among CKD patients.